Comparative Visualisation of Algorithms and Data Structures - Vateha, Filip; Šimoňák, Slavomír (Computing and Informatics, 2025)
Algorithms and data structures are principal parts of computer science education. For many students, however, it is not easy to master them due to their diversity and inherent complexity. The application of algorithm visualizations is a widely adopted approach, which can help to mitigate this difficulty. Within this work, we aim to improve the efficiency of the learning process in the field of algorithms and data structures. The main directions we use in this work to reach this goal are the introduction of comparative algorithm visualization and the implementation of the visualization tool based on contemporary standards. We analyze and compare several of the available solutions for algorithms and data structure visualization and evaluate them according to the provided functionalities. Further, we define a list of requirements, including the capability to compare selected algorithms visually. The practical outcome of this work is a web application that allows us to visualize and compare different algorithms and data structures in terms of their operation and efficiency. At the end of the paper, the proposed solution is evaluated in several ways.